2017
DOI: 10.1126/science.aan8311
|View full text |Cite
|
Sign up to set email alerts
|

Calibrated mitotic oscillator drives motile ciliogenesis

Abstract: Cell division and differentiation depend on massive and rapid organelle remodeling. The mitotic oscillator, centered on the cyclin-dependent kinase 1-anaphase-promoting complex/cyclosome (CDK1-APC/C) axis, spatiotemporally coordinates this reorganization in dividing cells. Here we discovered that nondividing cells could also implement this mitotic clocklike regulatory circuit to orchestrate subcellular reorganization associated with differentiation. We probed centriole amplification in differentiating mouse-br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
99
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(110 citation statements)
references
References 43 publications
10
99
0
1
Order By: Relevance
“…This is interesting because in cycling cells the daughter centriole needs to go through mitosis to mature into the mother centriole, which possesses appendages and can serve as a basal body . Possibly, this unexpected centriole maturation is rendered by the recently reported mitosis‐like program in the differentiating mEPCs . In addition, the bottom region of these cilia was usually Centrin‐positive (Fig C) .…”
Section: Resultsmentioning
confidence: 76%
“…This is interesting because in cycling cells the daughter centriole needs to go through mitosis to mature into the mother centriole, which possesses appendages and can serve as a basal body . Possibly, this unexpected centriole maturation is rendered by the recently reported mitosis‐like program in the differentiating mEPCs . In addition, the bottom region of these cilia was usually Centrin‐positive (Fig C) .…”
Section: Resultsmentioning
confidence: 76%
“…Concurrent maturation of the young centrosomal centriole and the procentrioles is also seen in cycling cells and was shown to be Plk1 dependent 24 . Since Plk1 regulates the A-to G-transition in brain MCC progenitors 5 , it is tempting to speculate that it also drives the concurrent maturation of the two generations of centrioles in these differentiating cells. Interestingly, such maturation of the daughter centriole is also observed in MCC induced from primary fibroblasts 11 .…”
Section: Discussionmentioning
confidence: 99%
“…This amplification occurs through the formation of intermediate organelles, the deuterosomes, which are composed of centrosome-related elements 2,3 . Deuterosomes support massive centriole production within a molecular cascade that is shared with the cell cycle centrosome duplication program [3][4][5] . Because two centrosomal centrioles seemed insufficient to scaffold the formation of tens of centrioles, massive centriole production through deuterosome structures was proposed to arise independently from the centrosome in MCC 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Having discovered a link between APC/C activity and centrosome stability, we investigated which APC/C substrate could account for the centrosome transport failure. Our prime candidate was Polo kinase (Plk1 in human): it is required for PCM recruitment to the centrioles (Prosser et al, 2012), is a known target of the APC/C in other organisms (Lindon and Pines, 2004), and in mammals is involved in the uncoupling of the centrosome cycle from the cell cycle during ciliogenesis (Al Jord et al, 2017). Furthermore, it was recently shown that Polo activity is crucial for centrosome stability in the Drosophila egg chamber (Pimenta-Marques et al, 2016).…”
Section: Polo Kinase Regulates Centrosome Stability and Transport Dowmentioning
confidence: 99%